2006
DOI: 10.2134/agronj2005.0234
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Seeding Rate Influences Herbicide Performance in Wild Oat (Avena fatua L.)

Abstract: Field experiments were conducted at three locations in Alberta for 3 yr to determine if spring wheat (Triticum aestivum L.) seeding rate (75 and 150 kg ha 21 ) influenced the effects of recommended and reduced herbicide rates on wild oat (Avena fatua L.) shoot biomass, wild oat seed in the soil seed bank, and wheat yield and net economic return. Wild oat biomass and seed in the soil seed bank decreased nonlinearly at both seeding rates as herbicide rates increased. The herbicides were more effective in reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Avena fatua seed production tended to be lower in competitive winter wheat stand (Site B). This is in line with findings of reduced A. fatua soil seed banks at higher wheat seeding rates implying reduced seed return [22]. It has been shown for other weeds as well that crop competition reduces weed seed production [23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Avena fatua seed production tended to be lower in competitive winter wheat stand (Site B). This is in line with findings of reduced A. fatua soil seed banks at higher wheat seeding rates implying reduced seed return [22]. It has been shown for other weeds as well that crop competition reduces weed seed production [23].…”
Section: Discussionsupporting
confidence: 89%
“…In seasons with reduced herbicide efficacy, biomass reduction of Lolium rigidum was higher in more competitive wheat cultivars compared to less competitive ones. Similarly, O'Donovan et al [22] showed that both ALS-and ACCase-inhibitors' efficacy on A. fatua increased with higher spring wheat seeding rate. Despite the very different winter wheat growth and competitiveness between our experiments, we did not find an effect of crop competitiveness on herbicide efficacy.…”
Section: Discussionmentioning
confidence: 94%
“…However, low plant populations may not always optimize grain yield. A number of studies report that higher plant populations enhance weed competitive ability and herbicide efficacy and produce higher grain yield (Beres et al, 2010b; O'Donovan et al, 2006). A study of variety selection and seeding rates ranging from 150 to 450 seeds m −2 reports that the ideal sowing density for solid‐stemmed wheat is in the range of 250 to 350 seeds m −2 (Beres et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing crop competitiveness with cultural tactics also improves herbicide efficacy (Derksen et al, 2002;O'Donovan et al, 2006). Scientists in the Netherlands are defining the minimum lethal herbicide dose needed for efficient weed control in various crops (Mortensen et al, 2000); lower weed density and improved crop competitiveness should enhance success of this approach also.…”
Section: Improved Herbicide Performancementioning
confidence: 99%